The influence of economic impact, cultural engagement, and community involvement on tourism sustainability: the role of tourist perception and environmental awareness - Rumpapak Luekveerawattana; Ken Taylor; Prateep Poprateep (Cogent Social Sciences)
Cultural tourism plays a significant role in economic development, community engagement, and sustainability. This study examines the relationships between economic impact, community involvement, cultural engagement, and sustainability indicators to understand their influence on cultural tourism experiences. Using a combination of cluster and convenience sampling, 400 valid responses were collected from tourists visiting cultural destinations. The findings indicate that economic impact positively affects community involvement, cultural engagement, and tourist perception, highlighting the importance of financial benefits in enhancing visitor experiences. Additionally, cultural engagement significantly influences tourist perception, reinforcing the role of authentic and diverse experiences in shaping satisfaction. However, the relationship between community involvement and sustainability indicators was not significant, suggesting that sustainability outcomes require integrated approaches beyond community participation alone. The study underscores the need for policies that support local businesses, promote authentic cultural experiences, and strengthen sustainable tourism practices. These insights contribute to the development of balanced tourism strategies that foster economic growth, cultural preservation, and environmental responsibility.